Pendampingan Digitalisasi Desa Berbasis Website Sebagai Upaya Meningkatkan Potensi Ekonomi Desa Parerejo Kecamatan Purwodadi - Nikmatul Izah; Mohamad Purwanto (LPPM Universitas Yudharta Pasuruan, 2021)
Parerejo Village is an area located in Purwodadi District, Pasuruan Regency, East Java. Parerejo village has very good economic potential as a tempe producing village and its variants. Almost the majority of the villagers are tempe craftsmen. The potential development of this village can be done by utilizing computer and information technology through the development of village websites. The village website can be a medium for promoting the potential and products of Parerejo Village. The method used during the implementation of this service is the Participatory Action Research .There are various achievements in this activity, increasing the understanding of village governments about the importance of village digitization by utilizing communication information technology through the creation of village websites. Through the Parerejo village website, it is hoped that the economic potential of the village can increase and village services can lead to excellent service for the community